Perbandingan Hasil Pemeriksaan Jumlah Eritrosit Dengan Teknik Homogenisasi Sekunder Empat Kali Dan Delapan Kali - Maria Nuraeni; Lidwina Septie (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Red blood cell counts are mostly laboratory tests. The pre-analysis step is subject to errors, especially homogenization. The homogenization technique used in the lab is the inversion technique. According to CLSI and BD Vacutainer, homogenizing is achieved by inverting the tube 8-10 times and by PerMenKes No. 43 up to 10-12 times. The EDTA blood is stored in the tube, if it is allowed to stand, a deposition process will occur, namely rouleaux, sedimentation, and compaction so that the results of the examination obtained are incorrect. Secondary homogenization is performed to ensure correct examination results. The purpose of this study is to determine if there is a difference in red blood cells in the secondary homogenized blood using inversion techniques four and eight times. The research was pre-experimental, with a Static group comparison design. The K2EDTA blood was 30 samples, which were secondarily homogenized by inversion technique 4 times and 8 times, after being allowed to be held for 30 minutes. Data analysis using Wicoxon test. The probability value of the Wilcoxon test was 0.000 <0.05. These results show that there are differences in erythrocyte count in the secondary homogenized blood 4 times and 8 times. Factors that may cause differences are imperfect deposit and homogenization. When blood is allowed to stand, there is a deposition process, which involves 3 steps, namely, rouleaux, sedimentation, and compaction, erythrocytes are at the bottom of the tube. Secondary homogenization 4 times, is not sufficient to completely homogenize, thus affecting the results of the red blood cell count examination. There are differences in red blood count in homogenized secondary blood 4 times and 8 times